Can the genes communicate with each other after birth? An international cross‐sectional study. Issue 2 (30th January 2023) - Hashim, Hashim Talib; Hashim, Ali Talib; Nazir, Abubakar; Afzaal, Usama; Nazir, Awais; Al‐Obaidi, Ahmed Dheyaa
Abstract: Background: Various factors contribute to the pathogenesis of a disease. These include genetic factors, family history, and some idiopathic causes. Genetic makeup has an important role in the progression of disease. This is due to mutations in genetic material, that is, deoxyribonucleic acid (DNA). Methodology: This is a cross‐sectional study that involved 5000 participants distributed across 250 countries. All the participants were randomly selected and asked to fill out the online survey. All the participants were fully informed about the study's purpose before providing their consent. Results: The participants were distributed among 250 countries. Their age mean (standard deviation) is 46.7 (12.4). We discovered a significant difference between those who have genetic or congenital diseases and those who have a family history of the disease. Also, there is a statistically significant difference between the recurrence of the disease and the duration of the visits of close relatives who have the same disease. Conclusion: The study suggests that there might be some ways, through gene waves or the environment, in which a gene changes the expression of other genes of similar sequence in different individuals when the required period of contact is provided. In the future, this theory might explain the idiopathic nature of some diseases.